Prevalence and Factors Associated with Pain and History of Musculoskeletal Injuries in Skateboarders - Alves Ferreira, B. D.; de Jesus Marques, J.; Teles Santos, T. R. (Revista Brasileira de Ortopedia (English Edition), 2021)
Objective (a) To identify the prevalence of current musculoskeletal pain and injury in the last year and (b) to verify the association of the presence of current pain and the history of injury with demographic, sports, and health characteristics in skateboarders.